Pakistanism: Ideological and Theoratical Discussions - Asma Amanat (بازیافت, 2017)
The term "Pakistanism" (Pakistaniyat) is directly related to the establishment of Pakistan. This term is so multidimensional that even today we can see the efforts of determining its denotations and discovering its connotations. To define Pakistanism is difficult without the definition of culture with reference to the debates on Pakistani thought and ideology. Culture comprises a people's customs and traditions which differentiate them from others. The ideological debate on Pakistanism seeks the answers to the questions as whether Pakistani culture is Islamic or Indian or an amalgam of both or none of them. This culture no doubt  represents a combination of Islam and geographic distribution that we call Indo-Islamic culture. The ingredients of Pakistanism i.e. doctrine, geography, history, language, literature, arts and social and ritual elements are discussed in the philosophical debates on Pakistanism. In short, Pakistanism means considering the existence of Pakistan and feeling the duty of its defense and other responsibilities.